Everyday Life of Women Workers in Badung Market (A Documentary Photography Study) - Febrian Putra; I Gede Yudarta; I Wayan Mudra (Institut Seni Indonesia Denpasar, 2023)
Capturing the everyday life of women workers in the badung market through documentary photography is a work that reveals the lives of women workers in the Badung Market in a powerful and effective way by using visual storytelling techniques. This technique involves using images and narration that complement each other to bring the audience into the story presented in images that can be used to present the lives of women workers in the Badung Market, while narration can be used to provide background on the lives of these women workers, as well as describe conflicts. they face in carrying out their work. The purpose of creating this work is to provide a visual depiction of the daily life of female workers, to use documentary photography as a medium to reveal the beauty and dignity of the work of female laborers as porters at Badung Market, Bali. The research method used in this study is a qualitative method with a case study approach. Data analysis techniques used include descriptive analysis, qualitative analysis, and thematic analysis. The result of creating this work focuses on the lives of female laborers transporting goods at the Badung Market in raising awareness about social issues, able to describe the activities carried out by women workers in the Badung Market in each photo so that they can provide in-depth information.